Cesium sorption intensification by complex natural sorbents from liquid radioactive media - Петрушка, Ігор Михайлович; Ятчишин, Юрій Йосипович; Петрушка, Катерина Ігорівна (Eastern-European Journal of Enterprise Technologies, 2014)
The studies have shown a growth (up to 90%) in the sorption degree of strontium ions by composite sorbents based on the modified titanium oxide of bentonite rocks and montmorillonite in a ratio of 1: 1. Optimum hydrodynamic regimes (350 rev/min), which increase the emergence effect of complex natural sorbents were determined. Intensification of external diffusion of cesium from liquid radioactive waste was calculated using the theory of local isotropic turbulence, taking into account the flow turbulence hydrodynamics and geometric parameters of mixers. The diffusion coefficient of strontium in the model solution, computed using the Wilkie and Chang dependence allows to predict the kinetics of external diffusion mass transfer of cesium ions in liquid medium based on the theoretical values of mass transfer coefficient. For a correlation of experimental and theoretical data of mass transfer coefficient during external diffusion mass transfer process, correction factor kβ (1,1-1,25) was calculated, which takes into account the radial distribution heterogeneity of solid dispersion particles in the system center and near the walls of the device depending on the particle size distribution and the size of the device.